EFEK PEMBERIAN P0C KULIT BAWANG MERAH PADA PERTUMBUHAN DAN PRODUKSI PAKCOY (Brassica rapa L.) - putri, septria wike; Ibnusina, Fedri; Alek Candra, Delni (Universitas Islam Balitar, 2025)
Pakcoy vegetables (Brassica rapa L.) are very popular among the public. Problems found in pakcoy cultivation are the habit of using inorganic fertilizers continuously, as well as acidic organosol soil types. To improve soil fertility and overcome the low yield of pakcoy, it is necessary to rehabilitate the land by using environmentally friendly shallot skin LOF. The main objective of this investigation to acquire the best concentration and the reaction of pakcoy vegetation to the union of NPK fertilizer and shallot skin LOF. This investigation utilized a Randomized Group Design with a treatment union of P1 100% NPK, P2 50% NPK + 15ml shallot skin LOF, P3 50% NPK + 20ml shallot skin LOF, P4 50% NPK + 25ml shallot skin LOF. The observation parameters are the number of leaves, leaf width, leaf length, plant fresh weight, and root length. The results revealed that the combined intervention of NPK fertilizer and onion skin LOF had no significant effect on the parameters of the number of leaves, leaf width, or root length. But this study had a significant effect on leaf length, and fresh weight of pakcoy plants. The optimal combination is 50% NPK combined with 20ml of shallot skin LOF. From the expected results of this study are, it is expected to be an option for farmers to reduce the use of NPK by using 20 ml of shallot skin LOF.